Peran Pendidikan Seksual “Sex Education” Anak Usia Dini Sebagai Upaya Preventif Atas Tindak Pidana Seksual - Erna Muchlis; St. Nurjannah (Alauddin Law Development Journal (ALDEV), 2022)
In this research is carried out with the aim of knowing (1). What is the Role of Sexual Education as a Preventive in Early Childhood Protection from Sexual Crime in the East Luwu District (2). How the Legal Provisions About Sexual Crimes in Early Childhood in Positive Law. This research is classified as an empirical juridical or field research. The data source of this research is primary data and secondary data by conducting interviews at the East Luwu Police and documentation. The data analysis technique used is qualitative analysis, namely analyzing data by describing in detail the state or reality of an object in the form of a sentence in order to provide a clearer picture and it is easy to draw a conclusion. The results showed that (1). The role of sexual education as a preventive in protecting early childhood from sexual crimes comes from the family environment, school, and the environment around the child (2). The legal provisions regarding sexual crimes in early childhood in positive law have been regulated by the Law on the Criminal Act of Sexual Violence against Children in terms of Law Number. 35 of 2014 concerning Child Protection and also the Application of Criminal Sanctions against Perpetrators of Sexual Violence Against Children.